Utilization of Fermented Cow Stool on the Growth of Moringa Oleifera - Maya Elfiyani Rambe; N. Ginting; E. Mirwandhono; S. Ginting (Talenta Publisher, 2020)
Fermented cow stool as organic fertilizer is more easily absorbed by plants, because the complex compounds have broken down and turns into liquid form. The research aim to observed the effect of organic fermented cow stool application on the growth of Moringa Oleifera. The research was conducted at the Bandar Khlifa Village, Deli Serdang Regency, North Sumatera Province from September to November 2020. The design used Completely Randomized Design in 4 treatments and 5 replications. The treatments consisted of P0 = Control (without fertilizer), P1 = 5 ml (fertilizer), P2 = 10 ml (fertilizer), P3 = 15 ml (fertilizer). The parameters observed were plant height, number of stem branches, leaf width and stem diameter. The results showed that the effect of fermented cow stool application had significant effect ( P < 0.05) on increasing plant height, leaf width, and stem diameter, but not significant on increasing number of stem branches and number of leaves. It is recommended to support good growth (plant height, leaf width and stem diameter) of Moringa Oleifera plants using a 5 ml dose of fermented cow feces fertilization.